Pengalaman hidup pasien kanker payudara di Kota Medan: Studi fenomenologi - Tarigan, Mula; Pasaribu, Maria Sarmaida (TROPHICO: Tropical Public Health J., 2023)
(Background) Breast cancer can cause death due to the rapid spread of cells and delayed treatment. Patients with breast cancer must adapt to the changes that occur in their daily lives. (Objective) The purpose of this tudy was to explore the lived experience of breast cancer patients in Medan. (Methods) This was a qualitative research with a descriptive phenomenological approach. The number of participants in this study were six people using purposive sampling. Data was collected using in-depth interview techniques and analyzed using the Colaizzi method. (Results) The results of this study found five themes, namely descriptions of breast cancer, emotional responses, effects of chemotherapy, social support, and spirituality. (Conclusion) Participants experienced biological and emotional changes in their lives after diagnosed breast cancer. However, they still have the ability to do positive things from within themselves and remain enthusiastic to follow the treatment program.